The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.analchem.0c01479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Hydrogen in High-Hydrogen-Content Material of Magnesium Hydride via Laser-Induced Breakdown Spectroscopy

Abstract: An analytical approach that can rapidly determine a wide range of hydrogen concentration in solid-state materials has been recently demanded to contribute to the hydrogen economy. This study presents a method for estimating hydrogen concentrations ranging from 0.2 to 7.6 mass % via laser-induced breakdown spectroscopy (LIBS) in a few seconds, with an improvement in the upper limit of determination (7.6 mass %) by approximately 1.3 times compared with a previous work (5.7 mass %). This extension of the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…3(f)) and the emission intensity was zero at 0 mass% of hydrogen. Additionally, we considered that the emission intensity of the H I 656.28 nm line increased linearly with an increase in hydrogen concentration in the model cathode because our previous study demonstrated that the emission intensities of the H I 656.28 nm line increased linearly with an increase in hydrogen concentration of up to 7.6 mass%, 37 as shown in Fig. S1 †.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3(f)) and the emission intensity was zero at 0 mass% of hydrogen. Additionally, we considered that the emission intensity of the H I 656.28 nm line increased linearly with an increase in hydrogen concentration in the model cathode because our previous study demonstrated that the emission intensities of the H I 656.28 nm line increased linearly with an increase in hydrogen concentration of up to 7.6 mass%, 37 as shown in Fig. S1 †.…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed that the effect of hydrogen originating from water molecules on the sample surfaces and in the measurement atmosphere on intensities of the H I 656.28 nm line can be minimized by storing the samples in a desiccator for over 3 days and attaching the moisture trap to the helium gas line. 37 Additionally, we used a pristine cathode, whose structure was almost the same as the model cathode after the fifth charging, as a reference sample to establish a calibration line for determining the hydrogen contents. Ni(OH) 2 is only involved in the charge reaction of the cathodes, and the molecular weight changes from 92.7 (Ni(OH) 2 ) to 91.7 (NiOOH) by the charge reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications of the analysis of hydrogen by LIBS involve hydrogen and deuterium analysis in plasma-facing materials for thermonuclear fusion devices [60,61,63,64], materials for nuclear fission reactors, such as Zircalloy [65], hydrogen in weldments [66], hydrogen-storage materials (MgH 2 ) [67], isotopic analysis of hydrogen in titanium [68,69], and even hydrogen analysis in H-bearing minerals on Mars by the rover Curiosity [70]. Isotopic analysis is traditionally a domain of mass spectrometry; however, the isotopic shift in the hydrogen spectrum also allows distinguishing between hydrogen and deuterium by optical emission.…”
Section: Laser-induced Breakdown Spectrometry (Libs)mentioning
confidence: 99%